The Important of Improving a Nutritional Status for Children with Disabilities - Nurul Hidayah; Baiq Fitria Rahmiati; Junendri Ardian; M. Thonthowi Jauhari; Qurratu Aini; M. Zulfikar Al-fariqi; Regina Pricilia Yunika; M. Kevin Saputra (LPPM Universitas Bumigora, 2020)
Disability is a special condition faced by some people. West Nusa Tenggara is at the top ten highest percentages for this special issue. This voluntary program was carried out to educate people how to maintain the diets of children in a special condition. The sharing programme was done by conducted a presentation, discussion, checking a height and weight and consultation. It was obtained that almost all parents having a kids with disability did not understand and were not aware how to prepare and choose food for their children. Approximately all children with a special issue at LombokCare community did not meet the standard height-for-age of World Health Organization (WHO), meaning that they were stunted. Therefore, a new insight and better care practices were gained by the parents in order to control and prepare the balanced diets of their special children.